ABC in context / Dr. Nalini Arumugam … [et al.] - Arumugam, Nalini; Subramaniam, Sathiyaperba; C Suppiah, Puspalata; Ramakrishnan, Prasanna (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Recognising letters is an essential component of the English language that students should know in order to begin developing basic language skills. However, it is observed that some children at pre-school level have not mastered this basic English language skill and this poses a stumbling block as they enter primary schools. English language educators adopt many approaches to enhance language acquisition, and one way is to create interesting activities to capture children's attention. It is viable to adopt an interactive approach through authentic pictures and letters accompanied with suitable sound. As the children follow the familiar objects, they learn known and unknown accompanying letters. Gradually they internalise these letters and improve their reading progressively. Even if they made mistakes, they are able to reattempt and strive to get answers by engaging in multi-trial opportunities without losing their self-esteem because there is no teacher or peers to evaluate them. This experiential learning enables children to self-assess their level and guides them through till they experience achievement. At the end, learning letters through authentic pictorial guidance as well as trial and error approach encourages children to learn independently to self-regulate their learning. This innovation is expected to have a good commercial value among young learners, teachers and parents.